2023
DOI: 10.2147/ahmt.s394883
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Sexual and Reproductive Health Rights Among University Students: A Cross-Sectional Study in Southeast Ethiopia

Abstract: In many situations, it can still be challenging to talk about sexual and reproductive health rights, and the little scientific research available indicates that university students have a poor understanding of these issues. Therefore, the aim of this study was to assess the knowledge of sexual and reproductive health rights among university students in southeast Ethiopia. Methodology: From February to March 2022, 483 study participants took part in an institutionally based cross-sectional study. The study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…Similarly, 14 studies reported condom utilization (20,23,24,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)). Among these, 3 studies described the prevalence of condom non-use during sexual activity and ranged from 23.3-57.2% (29)(30)(31) while the rest 10 studies described the prevalence of condom use during sexual activity and ranged 7.2-64.7% (20,23,24,28,(32)(33)(34)(35)(36)(37)(38).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Similarly, 14 studies reported condom utilization (20,23,24,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)). Among these, 3 studies described the prevalence of condom non-use during sexual activity and ranged from 23.3-57.2% (29)(30)(31) while the rest 10 studies described the prevalence of condom use during sexual activity and ranged 7.2-64.7% (20,23,24,28,(32)(33)(34)(35)(36)(37)(38).…”
Section: Resultsmentioning
confidence: 94%
“…Concerning behaviours, experiences, outcomes in the reviewed studies, surprisingly, all studies reported sexual activity and the prevalence was ranged from 18.9-79.5% (20,23,24,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).Among this, 2 studies had reported both the past (61.1% and 28.4%) and current (73.5% and 53.1%) status of sexual activity among participants (20,29) while the rest of studies (23,24,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) reported only the status of sexual activity at the time of the study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 A study conducted in Ethiopia to assess the knowledge of university student about the reproductive and sexual right found the level of awareness was low. 4 Another study reported that a high number of female university students in Egypt had poor knowledge about important issues in RH. 5 Likewise a program on reproductive health knowledge and attitude among women in rural Palestinian community found that there is low knowledge regarding postnatal health care, family planning method as well as poor knowledge concerning sexually transmitted diseases.…”
Section: Introductionmentioning
confidence: 99%